2004
DOI: 10.4049/jimmunol.172.8.4672
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: Early IL-4 Production Governs the Requirement for IL-27-WSX-1 Signaling in the Development of Protective Th1 Cytokine Responses following Leishmania major Infection

Abstract: There are conflicting reports on the requirements for the IL-27-WSX-1 pathway in the development of Th type 1 responses and resistance to intracellular pathogens; although early IFN-γ production and resistance to Leishmania major are impaired in the absence of WSX-1 signaling, WSX-1−/− mice generate robust IFN-γ responses and control infection with other intracellular protozoan pathogens. In this report, we resolve these conflicting observations and demonstrate that, in the absence of IL-4, WSX-1 is not requir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
120
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 92 publications
(128 citation statements)
references
References 18 publications
6
120
2
Order By: Relevance
“…4B). These findings demonstrated that early IFN-␥ production is intact in WSX-1 Ϫ/Ϫ mice infected with T. muris, and are consistent with recent reports that have identified WSX-1-independent Th1 responses in vivo (11,15,17).…”
Section: Enhanced Production Of Th2 Cytokines and Rapid Expulsion Of supporting
confidence: 81%
See 3 more Smart Citations
“…4B). These findings demonstrated that early IFN-␥ production is intact in WSX-1 Ϫ/Ϫ mice infected with T. muris, and are consistent with recent reports that have identified WSX-1-independent Th1 responses in vivo (11,15,17).…”
Section: Enhanced Production Of Th2 Cytokines and Rapid Expulsion Of supporting
confidence: 81%
“…For instance, following infection with L. major, which is characterized by the development of a mixed Th1/Th2 cytokine response, WSX-1 expression is required to promote optimal IFN-␥ production, most likely via STAT1-mediated induction of T-bet (10). However, blockade of IL-4 extinguishes the requirement for WSX-1 in promoting Th1 cell differentiation and immunity to L. major, demonstrating that the requirement for WSX-1 in type 1 immunity is restricted to a nonpolarized cytokine environment (11). Consistent with this proposed pathway, previous studies have shown that STAT1-dependent Th1 cell development is regulated by the presence of IL-4 (32).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Again, a decreased resistance of WSX-1-KO mice to infection with L. major was accompanied by a normal IFN-␥ response, whereas the expression of IL-4 was elevated 6 wk after infection (26). Neutralization of IL-4 abolished the requirement for WSX-1 to promote early IFN-␥ production and control of L. major (47), suggesting that WSX-1 signaling is dispensable for Th1 T cell differentiation in the absence of IL-4. In contrast to L. major infection, resolving infection with gastrointestinal nematodes is dependent on the genetically determined expression of IL-4 and IL-13 (48).…”
Section: Discussionmentioning
confidence: 93%